Acute Idiopathic Scrotal Edema. (13th November 2013) - Breen, Micheál; Murphy, Kevin; Chow, Jeanne; Kiely, Eamon; O'Regan, Kevin
Abstract : We report a case of acute idiopathic scrotal edema (AISE) in a 4-year-old boy who presented with acute scrotal pain and erythema. The clinical features, ultrasound appearance, and natural history of this rare diagnosis are reviewed. In this report, we highlight the importance of good ultrasound technique in differentiating the etiology of the acute scrotum and demonstrate the color Doppler "Fountain Sign" that is highly suggestive of AISE.